Adherence to heart failure management medications following cardiac resynchronization therapy. (1st February 2020) - Shah, Bimal R.; DerSarkissian, Maral; Tsintzos, Stelios I.; Xiao, Yongling; May, Damian; Lu, Xiaoxiao; Kinrich, David; Davis, Eric; Lefebvre, Patrick; Duh, Mei S.; Dasta, Joseph F.
Abstract: Objective: The purpose of this study is to assess the real-world impact of cardiac resynchronization therapy (CRT) on adherence to heart failure (HF) medications. Methods: MarketScan administrative health care claims data from 2008 to 2014 among patients with HF were used. The date of first CRT implantation served as the index date. Adherence to guideline-directed medical therapy (GDMT) classes were compared during pre- and post-index periods using proportion of days covered (PDC). Comparisons between the two periods were made using the Wilcoxon sign-rank test for continuous PDC and McNemar's test for dichotomized PDC. Results: Increases in medication adherence were observed for major classes of HF GDMT medications. Specifically, adherence to angiotensin-converting enzyme inhibitors (ACE-I), angiotensin receptor blockers (ARB), beta blockers (BB), and furosemide increased by 22, 24, 32, and 28% (all p  < .001), respectively, in the 12 months pre to 12 months post-CRT. Large increases between the pre- and post-CRT period were also observed when considering adherence as dichotomized PDC ≥0.80 in the 12 months pre- versus post-CRT. Conclusion: Adherence to HF medications significantly improved among HF patients post-CRT implantation. Further research is needed to better understand the underlying determinants of this effect, including whether the effect is attributable to factors such as enhanced patient monitoring and improved access to high-quality specialized HF care among patients receiving CRT.